Rose window graphs - Wilson, Stephen (Ars mathematica contemporanea, 2008)
This paper introduces a family of tetravalent graphs called "rose window graphs";, denoted ?$R_n(a, r)$?, and investigates their symmetry properties. Four families of these graphs are shown to be edge-transitive and it is conjectured that every ?$R_n(a, r)$? which is edged-transitive belongs to one of these families. Proofs and conjectures about the size of a dart-stabilizer and about regular maps containing these graphs are also offered.
Keywords: grafi; matematika; simetrija; teorija grafov